2009
DOI: 10.4155/fmc.09.97
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Chemically Modified Bioactive Peptides: Recent Advances, Challenges and Developments for Medicinal Chemistry

Abstract: Although not complying with Lipinski's rule, peptides are to an increasing extent being developed into new active pharmaceutical ingredients. This is mainly due to novel application routes, formulations and chemical modifications, which confer on the peptides improved uptake and increased metabolic stability. A brief survey of currently approved peptide drugs and the present scope of the application of peptides as drugs is provided. Cyclic peptides are emerging as an interesting class of peptides with conforma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
53
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 129 publications
2
53
0
Order By: Relevance
“…In comparison with the cyclic pentapeptides, all three cyclic hexapeptides 4-6 displayed distinctly reduced effects on adhesion of WM-115 cells to CagL. The lower affinities of 4-6 (Table 7) are in accordance with previous results on cyclic RGD peptides, where higher affinity to integrin a V b 3 was observed for cyclic pentapeptides like 1 because of conformational reasons (Haubner et al 1997;Gottschalk and Kessler 2002;Royo Gracia et al 2009). Previous spatial screening studies have shown that integrin a V b 3 preferentially binds peptides like 1 that present a bent RGD sequence, e.g.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…In comparison with the cyclic pentapeptides, all three cyclic hexapeptides 4-6 displayed distinctly reduced effects on adhesion of WM-115 cells to CagL. The lower affinities of 4-6 (Table 7) are in accordance with previous results on cyclic RGD peptides, where higher affinity to integrin a V b 3 was observed for cyclic pentapeptides like 1 because of conformational reasons (Haubner et al 1997;Gottschalk and Kessler 2002;Royo Gracia et al 2009). Previous spatial screening studies have shown that integrin a V b 3 preferentially binds peptides like 1 that present a bent RGD sequence, e.g.…”
Section: Resultssupporting
confidence: 91%
“…The approach makes use of an array of synthetic cyclopeptides, where cyclization combined with incorporation of a secondary structure-inducing element results in the well-defined spatial presentation of the recognition sequence (Haubner et al 1997;Xiong et al 2002). The recognition epitope RGD has been combined with a secondary structure-inducing element, as for example a D-amino acid or a b-amino acid (Haubner et al 1997;Schumann et al 2000;Urman et al 2007;Royo Gracia et al 2009). Several cyclic RGD peptides do not only display high affinity towards integrins, but also considerable selectivity between different integrin heterodimers.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…A brief overview of reaction protocols that have been developed for carrying out macrolactamization reactions is included, as well as important developments where chiral catalysts and biocatalysts have been used for the kinetic resolution of racemic amines using enantioselective N-acylation protocols. Given the enormous range of literature concerning amide, 8,[11][12][13][14][15][16][17] peptide, 3,[18][19][20][21][22][23][24] and protein synthesis, 7 it has proven necessary to direct interested readers to the many excellent books and reviews available that document this area. Consequently, the authors apologize in advance for being unable to directly cite many of the seminal contributions that have been published in this field and encourage readers to consult the many references cited within the comprehensive reviews referenced herein, as well as the numerous papers that cite them.…”
Section: Introductionmentioning
confidence: 99%
“…in cyclic peptides. 2 Moreover, the sense of chirality also renders them interesting starting materials for synthesis.…”
Section: Introductionmentioning
confidence: 99%